Determinan keberhasilan koperasi simpan pinjam wanita penerima dana perkuatan Perkassa dan hubungannya dengan pendapatan anggota - S Manar; M. Rachmad R.; Selamet Rahmadi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
The study aims to analyze: 1) the factors that influence the success of the Women’s Savings and Loan Cooperative receiving Perkassa retrofitting funds; 2) the influence of the success of the Women's Savings and Loans Cooperative recipient of Perkassa strengthening funds on members' income. The data used are primary and secondary data on women's savings and loan cooperatives in 6 regencies in Jambi Province, recipients of Perkassa retrofitting funds. The main analysis tool is the panel data regression model. The results of the study found that 1). the amount of percussion funds provided, and the operational costs of the Perkassa retrofitting funds issued have a significant positive effect, while the rate of return on congestion has a negative effect on the success of women's savings and loan cooperatives receiving percussion strengthening funds; 2). The success of cooperatives has a significant positive effect on the income of cooperative members